Identifikasi Mikroplastik pada Ikan Lajang (Decapterus russelli) dan Ikan Tembang (Sardinella fimbriata) di Pangkalan Pendaratan Ikan Oeba Kota Kupang - Priscalia, Renata; Wuri, Diana Agustiani; Toha, Larry Richard Wellem (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
Plastic waste in the ocean shows varying abundance at the surface, midwater, and sea floor. As plastic waste remains in the water for longer periods, it breaks down into smaller particels known as microplastic. This research aims to determine the presence, characteristic (shape and color), and abudance of microplastic in the gill and digestive tract organs of Indian scad (Decapterus russelli) and fringescale sardinella (Sardinella fimbriata) obtained from Oeba Fish Landing Base, Kupang City. The organs used were isolated with 10% KOH for 48-72 hours, and after disintegration, observations were made under a microscope. The results showed the presence of microplastics in both the Indian scad and fringescale sardinella. The microplastics found in the gills of the Indian scad included fibers and fragments in black, purple, and transparent colors, while in the digestive tract, fibers and fragments in black and transparent colors were found. The microplastics found in the gills of the fringescale sardinella included fibers and fragments in black, transparent, and green colors, while in the digestive tract, fibers, films, and fragments in black, transparent, and blue colors were found. The abundance of microplastics in the Indian scad was 0.9 particles/ind, consisting of 0.5 particles/ind in the gills and 0.4 particles/ind in the digestive tract. The abundance of microplastics in the fringescale sardinella was 1.4 particles/ind, consisting of 0.9 particles/ind in the gills and 0.5 particles/ind in the digestive tract